Rice value chain in Metema District, North Gondar, Ethiopia: Challenges and opportunities for innovation - Kassa, B. (Addis Ababa University, 2010)
Rice is a new crop for the country in general and the study area, Metema, in particular. There is an immense potential rice production area and high consumer demand. However, the rice sector is not fully developed as compared to the potential. Many institutional, organizational and technological factors were attributed to existing inefficiencies in rice production and utilization. This study was undertaken in Metema District of North Gondar Zone, Amhara National Regional State and has been designed to throw light on the challenges, opportunities and entry points for infusing further innovation (technological institutional and organizational) for upgrading the rice value chain. Identification of actors, their role, linkage, attitudes, habits and practices in the value chain; analyzing the institutional arrangements and enabling environment that affect the functioning of the value chain; and identifying recent innovation activities and their immediate outcomes in the District were the focus of this study. Primary data was collected from 100 randomly selected farm households and other rice value chain actors including input suppliers, marketing agents, consumers and support services. Data was collected using both qualitative and quantitative methods which incorporated semi-structured interview schedule, focus group discussions, key informant interview and personal observation. The main findings of the research revealed that, there are multiple public and non-public actors involved along the rice value chain, upstream from input supply to downstream consumers, playing different role. However, there is no mechanism to coordinate multiple actors together for effective and efficient functioning of the value chain. There is public sector actors’ domination with limited private sector involvement in the value chain. A long tradition of limited responsiveness, top-down, hierarchical, non participatory/ exclusiveness and less risk taking type of organizational culture and, habits and practices lead DoARD to have weak interaction, knowledge and information sharing with the various actors along the value chain. As to the linkage, weak and informal linkage between chain actors characterizes the rice value chain. Lack of post harvest processing technology( rice polisher), limited access to and supply of inputs, severe termite attack, non availability of well developed rice market, high labor demand for crop management, absence of responsible body who works on actors interaction were some of the challenges identified for innovation at various stages of rice value chain. Absence of rice polisher machine was the most critical problem that affects the whole value chain. On the contrary, increased farmer’s awareness about and availability of improved rice varieties, existence of favorable land and climatic condition, presence of high consumer demand, and increased institutional support from different GOs and NGOs were mentioned as opportunities for innovation. In order to address the existing problems and to increase competitive advantage of the rice production, plat forms and partnerships have to be created between value chain actors to create an enabling environment for sharing of information, knowledge and solve existing problems of shortage of rice polisher machine and input supply services. The existing extension service should also be strengthened in a way that enables working in harmony with relevant actors to bring about change for efficient and effective delivery of agricultural inputs/services.